2022
DOI: 10.1155/2022/7375879
|View full text |Cite
|
Sign up to set email alerts
|

LMX1B Activated Circular RNA GFRA1 Modulates the Tumorigenic Properties and Immune Escape of Prostate Cancer

Abstract: Prostate cancer (PCa) is the most common cancer affecting men, with increasing global mortality and morbidity rates. Despite the progress in the diagnosis and treatment of PCa, patient outcomes remain poor, and novel therapeutic targets for PCa are urgently needed. Recently, circular RNAs (circRNAs) have been studied in-depth as potential biomarkers for many diseases. In this study, circRNA microarrays using four pairs of PCa tissues were utilized to show that circGFRA1 was upregulated in PCa tumor tissues. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…ARHGEF26 is known to be over-expressed in prostate cancer and to be linked to cancer progression (Wang et al , 2012). LMX1B can bind to circGFRA1 and affect the tumorigenic properties and immune escape of PCa cells (Meng & Wu, 2022). Finally, NKX2–3 expression was found to correlate with PD-1 , making it an interesting marker for the efficacy of anti-PD-1 therapy in PCa (Wu et al , 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…ARHGEF26 is known to be over-expressed in prostate cancer and to be linked to cancer progression (Wang et al , 2012). LMX1B can bind to circGFRA1 and affect the tumorigenic properties and immune escape of PCa cells (Meng & Wu, 2022). Finally, NKX2–3 expression was found to correlate with PD-1 , making it an interesting marker for the efficacy of anti-PD-1 therapy in PCa (Wu et al , 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that hsa_circ_0005239 promotes proliferation and invasion and inhibits ferroptosis in HER‐2‐positive breast cancer via the circGFRA1‐miR‐1228‐AIFM2 axis (Bazhabayi et al, 2021). Moreover, circGFRA1 upregulated HECTD1 expression by sponging miR‐3064‐5p to regulate tumor cell proliferation migration and immune escape in prostate cancer (Meng & Wu, 2022). It also promotes HCC progression through miR‐498/NAP1L3 (Lv, Li, 2021) and miR‐149 in vitro (Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Through stimulation of GDNF in vitro, GFRA1 can signi cantly promote the proliferation, survival and dispersion of breast cancer cells, which may be relevant to the cooperative up-regulation of GDNF with the in ammatory cytokines TNF-α and IL-1β, activation of GFRA1 pathway, and promotion of breast cancer invasion and metastasis [42]. Men [43] et al have found that the GFRA1 promoter regulates the tumorigenic property and immune escape of prostate cancer by binding to LMX1B and up-regulating the expression of HECTD3064 by sponge miR-1-1p. These previous studies may partly reveal why patients in the low-risk group are vulnerable to immunotherapy, and further experimental veri cation of these mechanisms is needed.…”
Section: Discussionmentioning
confidence: 99%